2015
DOI: 10.1007/s10067-015-2946-6
|View full text |Cite
|
Sign up to set email alerts
|

Foot orthoses in the treatment of symptomatic midfoot osteoarthritis using clinical and biomechanical outcomes: a randomised feasibility study

Abstract: This randomised feasibility study aimed to examine the clinical and biomechanical effects of functional foot orthoses (FFOs) in the treatment of midfoot osteoarthritis (OA) and the feasibility of conducting a full randomised controlled trial. Participants with painful, radiographically confirmed midfoot OA were recruited and randomised to receive either FFOs or a sham control orthosis. Feasibility measures included recruitment and attrition rates, practicality of blinding and adherence rates. Clinical outcome … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
71
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 46 publications
(74 citation statements)
references
References 36 publications
2
71
0
1
Order By: Relevance
“…However, trials that did not use a control insole may be affected by methodological issues that may confound or bias the findings, such as placebo effect, ascertainment bias and resentful demoralisation 29. Trials that used a control insole may have mitigated these issues, but this is difficult to determine as no trial measured whether participant blinding was successful,51 whether the interventions were perceived as credible,52 or indeed, whether the control interventions had mechanical or physiological effects 50 52…”
Section: Discussionmentioning
confidence: 99%
“…However, trials that did not use a control insole may be affected by methodological issues that may confound or bias the findings, such as placebo effect, ascertainment bias and resentful demoralisation 29. Trials that used a control insole may have mitigated these issues, but this is difficult to determine as no trial measured whether participant blinding was successful,51 whether the interventions were perceived as credible,52 or indeed, whether the control interventions had mechanical or physiological effects 50 52…”
Section: Discussionmentioning
confidence: 99%
“…In relation to symptoms, two uncontrolled studies have suggested that foot orthoses can reduce foot pain in older people [85,86], and one randomised controlled trial found that foot orthoses with a medial arch support and metatarsal pad were effective at reducing foot pain and foot-related disability in older women with osteoporosis [87]. More recently, two randomised trials found that foot orthoses were effective at reducing symptoms in people with osteoarthritis of the first metatarsophalangeal joint [88] and midfoot joints [89]. These studies suggest that foot orthoses may be a useful conservative treatment for a range of foot disorders in older people.…”
Section: Foot Orthosesmentioning
confidence: 99%
“…In people with midfoot OA, short-term non-randomised studies demonstrated functional foot orthoses (FFO) improve pain and function [20] , [21] . Similarly, a recent feasibility study demonstrated that midfoot OA participants randomly assigned to the FFO group reported significantly greater improvements in clinical and functional outcomes compared to a sham intervention group [22] . Taken together, these findings suggest increased forces and/or pressures acting on the midfoot may contribute to increased mechanical loading on joints, and FFOs may support these structures thereby reducing pain and improving function.…”
Section: Introductionmentioning
confidence: 90%